Analysis of the leading sectors of Berau Regency Based on Location Quotient (LQ) Analysis Approach - Rosid, Tamam; Amin, Muhammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of the study was to determine the leading sub-sectors in Berau Regency. The data used were Gross Regional Domestic Product (PDRB) on the basis of Cash Prices for the 2010 Base Year (ADHK) according to the business field for the period 2017 to 2021 in Berau Regency & East Kalimantan Province as a comparison. Analysis tool used Location Quotient (LQ). The results of the Location Quotient (LQ) analysis in Berau Regency during the period 2017 to 2021 stated that the agriculture, forestry and fisheries sectors were the leading sectors because they had an LQ value >1, the agriculture, livestock, hunting, & agricultural services sub-sectors and the forestry and logging sub-sectors were the sub-sectors. superior because it has an average LQ value > 1, which means that the sector & sub-sector are classified as superior, specialized and sectoral contribution is higher than similar sectors at the provincial level. The fisheries sub-sector during the 2017-2021 period has an average value of LQ < 1, meaning that the sub-sector is classified as not superior, less specialized and the sectoral contribution of Berau Regency is lower than similar sectors in East Kalimantan province.